2021
DOI: 10.1200/op.20.00312
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intravenous Immunoglobulin Usage for Hypogammaglobulinemia After Implementation of a Stewardship Program

Abstract: PURPOSE: Intravenous immunoglobulin (IVIG) is used to replenish immunoglobulins in hypogammaglobulinemia (HG) caused by hematologic malignancies (HM) or their treatment (autologous stem-cell transplantation [ASCT] and chimeric antigen receptor T-cell therapy [CAR-T]), in an effort to reduce the risk of infections. However, there is limited evidence to support this use, and IVIG supplies are limited and shortages are common. METHODS: An IVIG stewardship program (ISP) was implemented with the following requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…One clinician particularly tied evidence, economic and legal aspects together by advocating for a strict evidence‐based approach to prescribing Ig, which would dampen demand: ‘ I think we should strive for more evidence‐baseness of using the IVIG, I think the present situation is still a little bit wild and uncontrolled…there will be a stop on that, it will be more strictly regulated…If IVIG would not be reimbursed for specific indications because the evidence is meagre or shallow, then of course, that will influence prescription’. (Expert 10) Literature provides examples of how some hospitals have initiated various stewardship programs to monitor and curb demand 59,71,72 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One clinician particularly tied evidence, economic and legal aspects together by advocating for a strict evidence‐based approach to prescribing Ig, which would dampen demand: ‘ I think we should strive for more evidence‐baseness of using the IVIG, I think the present situation is still a little bit wild and uncontrolled…there will be a stop on that, it will be more strictly regulated…If IVIG would not be reimbursed for specific indications because the evidence is meagre or shallow, then of course, that will influence prescription’. (Expert 10) Literature provides examples of how some hospitals have initiated various stewardship programs to monitor and curb demand 59,71,72 …”
Section: Resultsmentioning
confidence: 99%
“…This includes better understanding of psychological factors, group dynamics, and even logistical reasons for why various initiatives in hospitals to control demand are not successful for the long‐term 54 . Additionally, lessons can be learned and replicated from the hospital stewardship programs/organisational interventions that have sprung up, which exhibits varying levels of (dramatic) success in curbing Ig usage 59,71,72 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, most of the clinical data is derived from patients who underwent matched related HSCT, and clinical efficacy of IgRT for patients with HLA-haploidentical transplantation or CBT has not been fully examined. Finally, to develop an effective use of limited medical resources, a cost-effective approach such as IVIG stewardship program is desired [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that IVIG application according to the individual IgG level was a cost-effective approach. Aiming at reducing unnecessary IVIG usage, a stewardship IVIG program was carried out in the US [ 45 ]. In this program, the clinical application of IVIG was limited to designated two situations: (1) IgG < 400 mg/dL following autologous HSCT and CAR T-cell therapy; (2) IgG < 400 mg/dL with a history of a bacterial infection within the last 3 months.…”
Section: Current Status Of Igrt In Hsct Recipientsmentioning
confidence: 99%